Evaluating the Impact of a Structured Teaching Program on Knowledge and Attitude Toward the Utilization of Menstrual Cups Among Nursing Students in Chosen Nursing Colleges in Wayanad - Nidhina Paul; Anit Thomas; Anitta George; Anju Somaraj; Anna Celin Bejoy; Anna Jomy; Anu Thomas (International Journal of Midwifery Nursing And Practices, 2024)
Introduction: The current investigation aimed to evaluate the impact of a structured teaching program on the knowledge and attitude concerning the utilization of menstrual cups among nursing students in specific nursing colleges in Wayanad. The study objectives included evaluating the knowledge level, assessing the attitude, determining the effectiveness of the structured teaching program on knowledge and attitude regarding menstrual cup usage among nursing students, and exploring any association between pre-test knowledge on menstrual cups and selected demographic variables among nursing students. Materials and methods: A quasi-experimental design employing a one-group pre-test and post-test approach was selected for the study. The research was carried out at DM WIMS Nursing College in Wayanad, with a sample size of 100 participants selected through a convenient sampling technique. A demographic proforma consisting of 9 items, a knowledge questionnaire consisting of 15 self-administered questions and an attitude checklist consisting of 20 statements were used for the data collection. The samples were collected and the pre-test was followed by a structured teaching program regarding the menstrual cup. The post-test was conducted after one week. Result: Data were tabulated and analysed using descriptive statistics and the study revealed that, the knowledge and attitude level of the subjects increased after the structured teaching programme which was also found statistically significant (p<0.001). There is an association found between pre-test knowledge and monthly expenditure on sanitary products. The research findings revealed that the structured teaching programme administered is effective, which shows that our research fulfilled the objectives.
Keywords: Knowledge; Menstrual cup; attitude; structured teaching programme